1995
DOI: 10.1097/00006842-199505000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Association of Socioeconomic Status and Health

Abstract: The association of socioeconomic status (SES) with morbidity and mortality is a ubiquitous finding in the health literature. One of the principal challenges for biobehavioral researchers is understanding the mechanisms that link SES with health outcomes. This article highlights possible pathways by which SES may influence health. It also provides a discussion of sociodemographic and geographical modifiers of the SES-health relationship and offers several potentially fruitful directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
229
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(238 citation statements)
references
References 59 publications
4
229
2
3
Order By: Relevance
“…BP level is the strongest determinant of arterial stiffness during the aging process 8. Several studies have reported racial differences in BP,9, 10 and it is known that blacks are more affected by high BP levels than any other racial/ethnic group 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…BP level is the strongest determinant of arterial stiffness during the aging process 8. Several studies have reported racial differences in BP,9, 10 and it is known that blacks are more affected by high BP levels than any other racial/ethnic group 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that race and SES are highly correlated. Since measures of social class include education and income, and many minorities in the United States have lower socioeconomic status than Caucasians with regard to many measures of status, ethnic minorities are many times represented at the lower levels of the SES ladder (Anderson & Armstead, 1995). In particular, African Americans have lower income levels, educational attainment, occupational status, and wealth (Williams, 1998).…”
Section: Socioeconomic Status and Financial Barriers To Accessing Healtmentioning
confidence: 99%
“…There is a graded relationship between SES and health (Adler & Ostrove, 1999;Ginzberg, 1991;Kraus et al, 1980;Tyroler, 1989;Young, 1999). Those lower on the SES ladder, experience poorer health and more complications than those individuals higher in SES (Anderson & Armstead, 1995). SES has been a strong predictor of morbidity and premature mortality (Adler et al, 1993).…”
Section: Socioeconomic Status and Financial Barriers To Accessing Healtmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] A growing body of research recognizes the role that living in areas of concentrated poverty plays in producing social inequalities in health among different racial and ethnic groups in the United States. [6][7][8][9][10] Areas of concentrated poverty are often found in urban settings and are created through processes of racial segregation and economic disinvestment.…”
Section: Introductionmentioning
confidence: 99%